Precision drug delivery through methotrexate and tofacitinib citrate encapsulated mesoporous silica scaffold - Chakole, Dinesh; Rakte, Amol; Pande, Vishal; Kothawade, Sachin; Suryawanshi , Jayprakash (Journal of Applied Pharmaceutical Research, 2024)
Background: Advancements in drug delivery aim to enhance outcomes while reducing adverse effects. Mesoporous silica nanoparticles (MSN) offer potential for targeted delivery due to their unique properties, including ordered pore structure, large surface area, and biocompatibility. Methods: MSN were synthesized using tetraethyl orthosilicate (TEOS) and Pluronic F127, then amine-functionalized with 3-aminopropyltriethoxysilane. Methotrexate and tofacitinib citrate were loaded via incipient wetness impregnation. Characterization included FTIR, particle size analysis, TEM, SEM, DSC, XRD, and BET analysis. Results: FTIR confirmed surface modification. Particle size analysis showed nanoscale dimensions. TEM and SEM depicted ordered mesoporous structures. DSC indicated drug crystallinity and MSN amorphism. XRD revealed reduced drug crystallinity in MSN. BET analysis demonstrated high MSN surface area and pore volume. Drug-loading efficiency was 62.44%. Conclusion: Comprehensive synthesis and characterization of MSN for targeted drug delivery were achieved successfully, highlighting their potential in overcoming conventional therapy limitations.